3-D lanthanide coordination polymers with the flexible 1, 3-phenylenediacetate linker: Spectroscopic, structural and thermal investigations. (1st February 2019) - Łyszczek, Renata; Rusinek, Iwona; Sienkiewicz-Gromiuk, Justyna; Iwan, Mariola; Pavlyuk, Oleksiy
Graphical abstract: Four novel isostructural 3D coordination polymers of selected lanthanides and 1, 3-phenylenediacetic acid were obtained and characterized by vibrational (infrared and Raman) spectroscopy, powder and single-crystal X-ray diffraction methods. Their thermal behaviour was investigated by TG-DSC and TG-FTIR methods. Abstract: Four isostructural lanthanide coordination polymers of the formula [Ln2 (1, 3-pda)3 (H2 O)]·H2 O where Ln = Gd(1), Dy(2), Er(3), Lu(4) and 1, 3-pda = 1, 3-phenylenediacetate were hydrothermally synthesized and characterized by vibrational spectroscopy, thermal analysis, powder and single-crystal X-ray diffraction methods. All 1, 3-phenylenediacetates act as μ4 -linkers and connect the eight-coordinate lanthanide ions into the 3-D coordination networks. Carboxylate groups in the ligands molecules exhibit diverse conformations: both trans or trans and cis . Changes of Ln–O bond lengths among the investigated compounds point out to the lanthanide contraction. Infrared and Raman spectra confirmed that both carboxylic groups of ligand were deprotonated. The presence of the band of non-hydrogen bonded hydroxyl group from water molecule in the infrared spectra was discussed. Thermal behaviour of the complexes was investigated by the TG-DSC and TG-FTIR methods. The investigated complexes are thermally stable in air and nitrogen atmosphere up to 106–135 °C. Further heating of the complexes leads to dehydration and decomposition. Water, carbon oxides, m-xylene and methane are main volatile products of complexes thermal decomposition in nitrogen.